2020
DOI: 10.3390/cells9071647
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cellular and Molecular Mechanisms Underlying Inflammatory Bowel Diseases Development—A Focus on Ulcerative Colitis

Abstract: Inflammatory bowel diseases (IBD) are defined by the continuous inflammation of the gastrointestinal tract. During inflammation, the number of pathogens in the intestinal epithelium increases, leading to inflammasome assembly. Inflammasome activation is meant to protect the intestinal epithelial barrier from further damage by maintaining homeostasis. Although its purpose is to protect the cells, excessive nucleotide-binding oligomerization domain-like receptor and pyrin domain-containing protein 3 (NLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 121 publications
1
21
0
Order By: Relevance
“…It has been shown that inflammation and oxidative stress create a vicious cycle contributing to the pathogenesis of many inflammatory diseases including UC [ 36 ]. During colitis, proinflammatory factors activate phagocytes, which are recruited to the mucosa and result in ROS generation [ 9 ], causing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inflammation and oxidative stress create a vicious cycle contributing to the pathogenesis of many inflammatory diseases including UC [ 36 ]. During colitis, proinflammatory factors activate phagocytes, which are recruited to the mucosa and result in ROS generation [ 9 ], causing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, under pathological conditions, an increased level of NLRP3 will cause inflammation. The study also showed that the inflammatory response induced by abnormally activated NLRP3 played an important role in the onset, progression, and prognosis of IBD [ 29 ]. Various pathogenic factors act on the intestinal mucosa in UC patients, inducing abnormal activation of NLRP3 inflammasome and elevating the expression of IL-1 β and other inflammatory factors as well, subsequently causing topical intestinal mucosal damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, more and more studies have illustrated that that environmental factors such as infections or dysbiosis, which act on genetically susceptible individuals to induce the breakdown of natural immune tolerance, cause the immune dysfunction of the intestinal mucosa and trigger the onset and development of UC [ 15 ]. It is known that UC is a typical inflammatory disease, and it has been reported that the NLRP3 inflammasome can be recruited to the gut to promote UC progress by increasing pro-inflammatory cytokines [ 16 ]. Moreover, IRF5 can promote UC inflammation by modulating T cell signaling and by regulating secretion of cytokines [ 17 ].…”
Section: Introductionmentioning
confidence: 99%